A single-nucleotide polymorphism in WRKY33 promoter is associated with the cold sensitivity in cultivated tomato - Guo, Mingyue; Yang, Fengjun; Liu, Chenxu; Zou, Jinping; Qi, Zhenyu; Fotopoulos, Vasileios; Lu, Gang; Yu, Jingquan; Zhou, Jie (My University, 2022)
Natural variations in cis-regulatory regions often affect crop phenotypes by altering gene expression. However, the mechanism of how promoter mutations affect gene expression and crop stress tolerance is still poorly understood. In this study, by analyzing RNA-sequencing (RNA-Seq) data and reverse transcription quantitative real-time PCR validation in the cultivated tomato and its wild relatives, we reveal that the transcripts of WRKY33 are almost unchanged in cold-sensitive cultivated tomato Solanum lycopersicum L. 'Ailsa Craig' but are significantly induced in cold-tolerant wild tomato relatives Solanum habrochaites LA1777 and Solanum pennellii LA0716 under cold stress. Overexpression of SlWRKY33 or ShWRKY33 positively regulates cold tolerance in tomato. Variant of the critical W-box in SlWRKY33 promoter results in the loss of self-transcription function of SlWRKY33 under cold stress. Analysis integrating RNA-Seq and chromatin immunoprecipitation sequencing data reveals that SlWRKY33 directly targets and induces multiple kinases, transcription factors, and molecular chaperone genes, such as CDPK11, MYBS3, and BAG6, thus enhancing cold tolerance. In addition, heat- and Botrytis-induced WRKY33s expression in both wild and cultivated tomatoes are independent of the critical W-box variation. Our findings suggest nucleotide polymorphism in cis-regulatory regions is crucial for different cold sensitivity between cultivated and wild tomato plants.
Keywords: W-box; WRKY33; Cold tolerance; Natural variation; Promoter; Tomato